DEVELOPING ENGLISH MATERIAL FOR NURSING STUDENTS - Rahmawati, Amalia; Syafiq, Ahmad Nur (JURNAL SMART, 2018)
This research aims to develop the learning material based on the KKNI curriculum and need analysis. This research belongs to research and develoment (RND). The population and sample in this research were the sixth semester nursing students of STIKES Muhammadiyah Kudus. This research concluded that 1) the learning material must be created based on KKNI curriculum and need analysis to prepare the students in the work field, 2) the material needs to increase not only English skill but also nursing skill, 3) the use of learning material that has been developed in the experimental group shows significant different from the control group.